The Effect of Combined High-Intensity Interval Training Exercises on Some of the Technical Skills and Endurance of Performance for Advanced Futsal Players - Hasan Hadi Saleh; Mahmoud Nasser Radhi; Ali Wafaa Abdullah (Indian Journal of Forensic Medicine & Toxicology, 2021)
The importance of the research lies in scientifically preparing a complex of high-intensity interval training, asresearchers believe that it affects some technical skills that are directly involved to endurance the performanceof futsal players. As for the research problem: Through the experience of field researchers, they noticed thatthere is a noticeable decrease in the performance of skills in the second half and in the matches in whichthe level of technical performance is very high, and this decrease leads to slow movement to take the rightplace during the performance of those skills, the researchers believe that the reason for this is that these skillsdo not receive their adequate share of training in a manner consistent with the nature of their performancefrom the physical and physiological standpoint. The aim of which is to have a positive effect on some of thetechnical skills and performance of futsal players. The researchers used the experimental method to solvethe research problem, and on the research community, the research community was identified with the 14players of Naft Al Wasat club in the futsal season 2020-2021, they were distributed into two groups equallyin a random way (lottery method), and then data was processed using appropriate statistical methods.